Connectivity changes following transcranial alternating current stimulation at 5-Hz: an EEG study - Tien-Wen Lee; Gerald Tramontano (AIMS Neuroscience)
Transcranial alternating current stimulation (tACS) at 5-Hz to the right hemisphere can alleviate anxiety symptoms. We aimed to explore the connectivity changes following the treatment. We collected electroencephalography (EEG) data from 24 participants with anxiety disorders before and after the tACS treatment during a single session. Electric stimulation was applied over the right hemisphere, with 1.0 mA at F4, 1.0 mA at P4, and 2.0 mA at T8, following the 10-10 EEG convention. With eLORETA, the scalp signals were transformed into the cortex's current source density. We assessed the connectivity changes at theta frequency between the centers of Brodmann area (BA) 6/8 (frontal), BA 39/40 (parietal), and BA 21 (middle temporal). Functional connectivity was indicated by lagged coherences and lagged phase synchronization. Paired t-tests were used to quantify the differences statistically. We observed enhanced lagged phase synchronization at theta frequency between the frontal and parietal regions (P = 0.002) and between the parietal and temporal regions (P = 0.005) after Bonferroni correction. Applying tACS 5-Hz over the right hemisphere enhanced inter-regional interaction, which was spectrum-specific and mainly mediated by phase rather than power synchrony. The potential neural mechanisms are discussed.